In vitro Studies on the Effect of Insecticides on the Growth of Fungal Pathogen Stemphylium vesicarium (Wallr.) Simmons - Mishra, Bhavya; Singh, R. P. (International Journal of Bio-resource and Stress Management, 2018)
Onion is one of the most important commercial crops grown all over the world. The crop is attacked by many diseases and insect pests which cause yield losses and quality deterioration. Stemphylium blight caused by Stemphylium vesicarium (Wallr.) Simmons has emerged as a serious problem in the past decade. Thrips infestation is also common in onion crop and therefore, use of insecticides is a common practice. The physical injuries caused by feeding of thrips can predispose the onion plants to Stemphylium blight and therefore it is only logical that reduction in thrips infestation may reduce the disease as well. Since, the insecticides used to manage thrips may also have some direct effect on the fungal pathogen Stemphylium vesicarium, therefore insecticides were tested in vitro at different doses by poison food technique to assess their effect on fungal growth. The results of the study revealed that insecticides do have a direct inhibitory effect on mycelial growth of the test fungi. Profenophos gave highest percent mycelial inhibition (58.39%), followed by pymetrozine (52.92%). At the recommended doses for the control of onion thrips, profenofos provided 51.82% inhibition and pymetrozine, carbosulfan and nimbicidin provided almost 50% inhibition. These results provide an insight about the possible effects that insecticides can have on the fungal pathogen and their potential use in the disease management strategy under field conditions.